Impacto de las herramientas digitales en la enseñanza y el aprendizaje de la química en educación secundaria: Impact of digital tools on teaching and learning chemistry in secondary education - Delgado Mora, Marta Isabel; Alcocer Tocora, Milena (Encuentro Educacional, 2024)
Science teaching, and chemistry in particular, faces the challenge of making often abstract and complex concepts accessible and understandable. Traditional methods sometimes fail to engage students or facilitate learning. This study aimed to explore the impact of digital tools on the teaching and learning of chemistry in secondary education over the last 5 years. The methodology used was a qualitative, documentary-type approach with a descriptive scope. Through the literature review, several studies are examined that analyze how these technological tools have improved student skills and the quality of teaching. Several strengths were identified: significant increase in student participation, greater conceptual understanding of complex topics, increased accessibility to educational resources, interactive, dynamic and attractive learning materials, which enrich the educational experience and make it more inclusive. However, the study also identifies important challenges that need to be addressed to maximize the positive impact of digital technologies, highlighting issues related to the digital divide, which still affects many regions, particularly Colombia, limiting equitable access to technology. Adequate training of teachers and students in the effective use of these tools is urgently needed, in order to effectively integrate them into their school practices.